Dampak Kepemimpinan, Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Kasus PT. Suconfindo Padang) - Zusmawati Zusmawati; Imili Riski Ramadani (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
The purpose of this research is to examine the impact of the variable Leadership on employee performance (Case Study of PT. Suconfindo Padang). to examine the impact of the variable Motivation on performance (Case Study of PT. Suconfindo Padang), to examine the impact of the Variable of Work Discipline on performance (Case Study of PT. Suconfindo Padang). Collecting data by distributing questionnaires to 38 respondents, by using test instrument test (validity test and reliability test), descriptive analysis, classical assumption test (normality test, multicollinearity test and heteroscedasticity test) multiple linear regression and t test, with the help of the SPSS application. The results of the study show that leadership has a positive and significant impact on employee performance (Case Study of PT. Suconfindo Padang), motivation has a positive and significant impact on employee performance (Case Study of PT. Suconfindo Padang), work discipline has a positive and significant impact on employee performance employee performance (Case Study of PT. Suconfindo Padang).